Practicing Asian Gastrodiplomacy through UTY Growpath Expo #3: Culinary Culture, Soft Power, and Nation Branding - Muhammad Ridha Iswardhana; Aspin Nur Arifin Rivai (Bulletin of Social Studies and Community Development, 2026)
In the globalization era, cultural identity has become a strategic resource for strengthening national image and international influence through non-coercive means. Gastrodiplomacy is increasingly relevant because food can convey cultural values, collective identity, and social meanings in ways accessible to wider publics. This study aims to analyze UTY Growpath Expo #3 as a medium of gastrodiplomacy, soft power, and nation branding through the introduction of traditional Asian foods. The research used a qualitative approach with an action research design. Data were collected through observation, interviews, and documentation involving student organizers, supervising lecturers, culinary presenters, and visitors who participated in the expo. The data were analyzed inductively by identifying themes related to planning, implementation, interaction, cultural communication, and evaluation. The findings show that UTY Growpath Expo #3 served as a micro-level arena for practicing gastrodiplomacy through culinary products from Afghanistan, China, South Korea, and Vietnam. Food presentation, cultural storytelling, traditional attire, sustainable packaging, and direct interaction enabled visitors to understand cultural identities beyond taste and consumption. Positive visitor responses indicated that culinary-based activities can promote intercultural understanding, strengthen cultural attraction, and connect entrepreneurship education with public diplomacy practices. The study concludes that educational exhibitions can serve as alternative spaces for implementing gastrodiplomacy and nation branding at the local level. The novelty of this study lies in positioning a university-based expo as a non-state arena in which students serve as cultural communicators, translating Asian culinary diversity into soft-power practice within an applied, participatory, and locally grounded learning context. Keywords: Asian Gastrodiplomacy, Nation branding, Soft power, Diplomacy practice in higher education, UTY Growpath Expo